Bartleby: Easter eggs and other treats. (Economist, 2022)
In the article, the author discusses the move by companies like WordPress and Google to incorporate playfulness in their products like the unexpected messages or features called Easter eggs. According to University of Waterloo's Daniel Vogel and Matthew Lakier, Easter eggs are used to reward users' curiosity, recruit staff, and acknowledge the work of developers. Also cited is the move by Microsoft to stop the use of Easter eggs from its software in 2002 under its Trustworthy Computing program.